Pengaruh Tata Kelola Perusahaan terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (Studi Perbandingan pada Bank Umum Syariah Milik Pemerintah dan Milik Swasta) - Nurdin Nurdin (el-Jizya: Jurnal Ekonomi Islam, 2018)
Previous studies highlight the relationship between Corporate Governance and Corporate Social Responsibility. Good corporate governance has been found significantly influence the level of a company social responsibility whether in conventional or Islamic companies context. Most of the studies focus of the studies focus on conventional banks or Islamic banks belong to government or provate actors. However, limites or even none of the studies has tried to compare the impact of corporate governance on social responsibility between government and private owned syariah banks. Through quantitative method, we studied the differences between government and private owned syariah banks using six syariah banks samples. The sample was purposively selected from Indonesian Bank website. Our data analysis shows that all three variables; independent commissioners, boards of directors, and sharia supervisory boards are significantly impact the companies’ corporate social responsibility pactices. Eventhough, the difference between government and private owned syariah banks in social responsibilty practices is not significant, the result shows that the level compliance of government syariah banks towards social responsibiity is higher than private syariah banks. This might prove that government syariah banks might more commit to social welfare than private syariah banks. Future reseach with more samples and variables might be required to make the finding more valid.